Demokrasi Radikal sebagai Alternatif Tatanan Politik Global dalam Konteks Multikulturalisme - Dewi Setiyaningsih (Journal of Integrative International Relations, 2021)
This article discusses the relevancy of cosmopolitan democracy concept in multicultural world. It argues that cosmopolitan democracy concept is not enough in achieving a just and equal political order the context of plural world-citizenship, it showed by the practice of economic, social and political structure which prevails. Hence, this article tried to search an alternative in attempt to make the idea of cosmopolitan democracy become more realistic and inclusive by adopting radical democracy concept. Firstly, it discuss the critics of Kant’s cosmopolitan view using Spivak’s conception of Planetarity. Secondly, it discuss about the plural democracy by Mouffe’s in the context of planetarity. This combination that yields a plural democracy in the context of world-citizenship.